Chito-oligosaccharide by Chitosan Depolymerization Induced with Hydrogen Peroxide for application as Bio-preservative (Antimicrobial) on Traditional Fish boiled - Faqih Ali Ridho; Bambang Riyanto; Uju Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Chitosan has been developed for food product, agriculture, environment, and industry as medical,pharmaceutical, and cosmetics. The depolymerization of chitosan to chito-oligosaccharide was produce onsoluble product and has better function as antimicrobial. The objective of this research was to COS withhydrogen peroxide depolimerization for preservatives of fish boiled. Research method included chitosandepolymerization, characterization of COS, and characterization of traditional fish boiled quality. Theoptimum concentration of chito-oligosaccharide was 2% H2O2 with sonication at frequencies of 20kHz.The treatment produced yield 93.27±0.9%, molecular weight 2.83±0.1 kDa, polymerization degree 17±0.6,and it inhibited the growth of E. coli, S. aureus, and B. cereus. The dipping with 0.25% produce the best fishboiled quatity.